Schlafen 3 induction by cyclic strain regulates intestinal epithelial differentiation - Yuan, Lisi (Am J Physiol Gastrointest Liver Physiol, 2010)
The intestinal epithelium is subjected to repetitive deformation during normal gut function by peristalsis and villous motility. In vitro, cyclic strain promotes intestinal epithelial proliferation and induces an absorptive phenotype characterized by increased dipeptidyl dipeptidase (DPPIV) expression. Schlafen 3 is a novel gene recently associated with cellular differentiation. We sought to evaluate whether Schlafen 3 mediates the effects of strain on the differentiation of intestinal epithelial cell (IEC)-6 in the absence or presence of cyclic strain. Strain increased Schlafen 3 mRNA and protein. In cells transfected with a control-nontargeting siRNA, strain increased DPPIV-specific activity. However, Schlafen 3 reduction by siRNA decreased basal DPPIV and prevented any stimulation of DPPIV activity by strain. Schlafen 3 reduction also prevented DPPIV induction by sodium butyrate (1 mM) or transforming growth factor (TGF)-β (0.1 ng/ml), two unrelated differentiating stimuli. However, Schlafen-3 reduction by siRNA did not prevent the mitogenic effect of strain or that of EGF. Blocking Src and phosphatidyl inositol (PI3)-kinase prevented strain induction of Schlafen 3, but Schlafen 3 induction required activation of p38 but not ERK. These results suggest that cyclic strain induces an absorptive phenotype characterized by increased DPPIV activity via Src-, p38-, and PI3-kinase-dependent induction of Schlafen 3 in rat IEC-6 cells on collagen, whereas Schlafen 3 may also be a key factor in the induction of intestinal epithelial differentiation by other stimuli such as sodium butyrate or TGF-β. The induction of Schlafen 3 or its human homologs may modulate intestinal epithelial differentiation and preserve the gut mucosa during normal gut function.